The role of synaptic protein NSF in the development and progression of neurological diseases - Yang, Jingyue; Kong, Lingyue; Zou, Li; Liu, Yumin (Frontiers in Neuroscience, 2024)
This document provides a comprehensive examination of the pivotal function of the N-ethylmaleimide-sensitive factor (NSF) protein in synaptic function. The NSF protein directly participates in critical biological processes, including the cyclic movement of synaptic vesicles (SVs) between exocytosis and endocytosis, the release and transmission of neurotransmitters, and the development of synaptic plasticity through interactions with various proteins, such as SNARE proteins and neurotransmitter receptors. This review also described the multiple functions of NSF in intracellular membrane fusion events and its close associations with several neurological disorders, such as Parkinson’s disease, Alzheimer’s disease, and epilepsy. Subsequent studies should concentrate on determining high-resolution structures of NSF in different domains, identifying its specific alterations in various diseases, and screening small molecule regulators of NSF from multiple perspectives. These research endeavors aim to reveal new therapeutic targets associated with the biological functions of NSF and disease mechanisms.